Opportunities proteomic the analysis of fibers of urine for an estimation of progressing of a chronic heart failure - M. M. Batyushin; N. S. Vrublevskaya; I. V. Sarvilina (Медицинский вестник Юга России, 2011)
Purpose: To reveal, what changes of fibers of a pattern of urine at sick are connected by a chronic heart failure (CHF) with increase of a functional class (FC) of disease.Materials and Methods: 90 patients with CHF II-IV FC are surveyed. Control group practically healthy 30 patients. Differentiated allocation separate proteins and fibers of urine of patients made by means of weights-spectrometry.Results: At patients CHF in structure of fibers of urine markers of alteration of kidneys, connected with structural transformation. Progressing CHF up to a final stage it is connected with increase of occurrence β-sarcoglican, similar to tolloids fiber 2 and L-antigen. Among contracting fibers in process of increase FC CHFoccurrence cation-transport ATP decreases, and isoforms 1 fiber 6, connected with microtubuls – raises, that causes reduction of activity of receipt of calcium in sarcoplasmic rethiculum in nephrocytes and endoteliocytes vessels of kidneys.Summary: Changes of an albuminous spectrum of urine at patients CHF it is information are significant for the forecast of progressing of a basic disease.